A deep dive into the ancestral chromosome number and genome size of flowering plants. Issue 3 (16th June 2020) - Carta, Angelino; Bedini, Gianni; Peruzzi, Lorenzo
Summary: Chromosome number and genome variation in flowering plants have stimulated growing speculation about the ancestral chromosome number of angiosperms, but estimates so far remain equivocal. We used a probabilistic approach to model haploid chromosome number ( n ) changes along a phylogeny embracing more than 10 000 taxa, to reconstruct the ancestral chromosome number of the common ancestor of extant angiosperms and the most recent common ancestor for single angiosperm families. Independently, we carried out an analysis of 1C genome size evolution, including over 5000 taxa. Our analyses revealed an ancestral haploid chromosome number for angiosperms of n  = 7, a diploid status, and an ancestral 1C of 1.73 pg. For 160 families, inferred ancestral n are provided for the first time. Both descending dysploidy and polyploidy played crucial roles in chromosome number evolution. While descending dysploidy is equally distributed early and late across the phylogeny, polyploidy is detected mainly towards the tips. Similarly, 1C genome size also increases (or decreases) significantly in late‐branching lineages. Therefore, no evidence exists of a clear link between ancestral chromosome numbers and ancient polyploidization events, suggesting that further insights are needed to elucidate the organization of genome packaging into chromosomes. Abstract : See also the Commentary on this article by Escudero & Wendel, (2020), 228 : 805–808 .